The "Cinderella Effect": The Value of Unexpected March Madness Runs as Advertising for the Schools. (December 2020) - Collier, Trevor; Haskell, Nancy; Rotthoff, Kurt W.; Baker, Alaina
This study looks at the impact of a university making a surprise ("Cinderella") run in the men's NCAA basketball tournament. Our results suggest that surprise success in the tournament has little to no impact on the quantity of applications in subsequent years. However, we find that freshmen enrollments increase for private schools two academic years after a Cinderella run (with mixed results on the quality of freshmen—although not worse). Given an average private school, with 1, 253 freshmen and paid tuition of 24, 428 (each year) plus room and board, a Cinderella run is worth approximately 7.3 million in 2012-dollars.